Extrapulmonary and atypical clinical presentations of COVID‐19. Issue 11 (29th June 2020) - Abobaker, Anis; Raba, Ali Ahmed; Alzwi, Aboubaker
Abstract: The novel coronavirus (SARS‐CoV2) has led to an outbreak of multiple cases of pneumonia in Wuhan city in December 2019. The disease caused by this virus was named coronavirus disease 2019 or "COVID‐19", which was declared by the World Health Organization as a global pandemic in March 2020. It typically presents with respiratory symptoms and febrile illness. However, there are few reported extrapulmonary and atypical presentations, such as hemoptysis, cardiac, neurological, gastrointestinal, ocular, and cutaneous manifestations, as well as venous and arterial thrombosis. Lack of awareness of these presentations might lead to misdiagnosis, delayed diagnosis, and isolation of suspected patients which increases the risk of transmission of infection between patients and doctors. All these issues will be discussed in this review.